Marketplaces as sites for the development‐adaptation‐disaster trifecta: Insights from Vanuatu. (6th October 2020) - McNamara, Karen E.; Clissold, Rachel; Westoby, Ross
Abstract : Faced with the pressing challenges of poverty, climate change and disasters, identifying opportunities for interventions that offer positive outcomes across the trifecta of development, adaptation and disaster risk reduction is critically needed. While the overlaps between these streams can be straightforward in theory, practical opportunities for convergence are often lacking. Drawing on 10 focus groups with women market vendors who are part of the UN Women's Markets for Change programme in Vanuatu, this paper explores how markets as places can be useful entry points for this trifecta. Marketplaces can be important sites for developing capabilities and empowering women. As transient and interactive spaces, marketplaces also have inherent strengths that can be built upon and utilised to heighten intervention reach and foster positive outcomes across the development‐adaptation‐disaster trifecta. This paper encourages further exploration into the capacity of marketplaces to achieve this trifecta of outcomes across various scales and locations, and to find solutions to existing challenges.